Click chemistry inspired synthesis of andrographolide triazolyl conjugates for effective fluorescent sensing of ferric ions. Issue 21 (1st November 2022) - Pandey, Nishant; Jyoti,; Singh, Mangat; Dwivedi, Pratibha; Sahoo, Subash C.; Mishra, Bhuwan B.
Abstract: The naturally occurring compound andrographolide 1 was used as a substrate for the synthesis of a novel terminal alkyne 3 which on copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) reaction with azides 4a-l, 7 and 9 furnished a series of regioselective andrographolide triazolyl conjugates 5a-l, 8 and 10, respectively. A free glycoconjugate 6 was also prepared by selective deprotection of compound 5i in good yield. All the compounds were characterized by absorbance, FT-IR, NMR, and HR-MS analyses. The triazolyl conjugate 8 was further investigated as a probe for selective detection of Fe 3+ ion in matrix. The mode of attachment of Fe 3+ ion to the compound 8 was established by absorbance, fluorescence, infrared (IR), and nuclear magnetic resonance (NMR) spectroscopy, and high resolution mass-spectrometry (HR-MS). The logic gate circuits were constructed for the probe 8 and ethylenediaminetetraacetic acid (EDTA). The environmental perspective of probe 8 was investigated in real water samples. Graphical Abstract: UF0001